Bank Loan-Loss Provisions: A study of Korean Commercial Banks - Do, Phuong Nhu (2013)
This paper studies the bank loan-loss provisioning behaviour of 16 Korean commercial banks over the 2006Q2-2011Q2 period using both bank-specific and macroeconomic variables. Two regression methods: Generalised Least Squares- Random Effects model and the Dynamic Panel Data Arellano-Bond model are applied. The empirical analysis on LLPs of Korean banks in this paper mainly focus on the following issues: 1) whether LLP is influenced by the income smoothing practice; 2) the relationship between LLP practice and the economic cycle; 3) whether Korean banks use provisions to manage their capital given the minimum regulatory capital requirements; 4) whether LLP level in Korean banks are affected by their provision level of the last period. Evidence of income smoothing practice, procyclicality is present but there is no evidence of capital management. The result also suggests Korean banks adjust provision level based on that of the previous year.